Lord Krishna as Brahman in the Bhagavadgita - Paudyal, Ganga Ram (The Outlook: Journal of English Studies, 2020)
This article explores Lord Krishna as Brahman in the Bhagavadgita who is regarded as the source of cosmic consciousness. The concept of the Brahman resembles the idea of the absolute reality. In the Bhagavadgita, the chief speaker, Lord Krishna, projects himself as the ultimate reality from where the entire creation radiates. In this regard, Lord Krishna is the Brahman. He addresses the question as to what constitutes the virtuous path and necessary spiritual liberation to release from the cycles of rebirth and attain the redemption (moksha). The message of the Bhagavadgita or the lesson of Lord Krishna’s teaching mainly focuses us to follow the path of righteousness by giving up desires and selfishness which can be the obstacles of dharmic action and spiritual living. In the Bhagavadgita, Lord Krishna emphasizes that he is everywhere both in manifested and invisible world as a guiding force—Brahman. He is all in all and all is in him as being the nucleus of the universe from whom nobody can escape. He shows different spiritual paths for human beings to liberate from these worldly chains like jnana yoga, bhakti yoga, karma yoga and raja yoga which converge in one and lead to divinity. As a qualitative research, this paper explores, interprets and, expounds the concepts and phenomena from the Bhagavadgita to justify Lord Krishna as the source of ultimate reality—Brahman.